A three-dimensional covalent organic framework@metal halide perovskite composite material and its preparation method and application
By growing perovskite quantum dots in situ in three-dimensional covalent organic frame materials, the problem of low photocatalytic performance of MAPbX3 quantum dots is solved, efficient CO2 adsorption and photocatalysis are achieved, simplifying the preparation process and achieving high-efficiency light at room temperature catalytic.
Patent Information
- Application Number
- CN202311064152.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-23
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-08-23
Smart Images

Figure CN117181303B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organic-inorganic composite materials, and in particular to a three-dimensional covalent organic framework@metal halide perovskite composite material and a preparation method and application thereof. Background Art
[0002] Photocatalytic reduction of carbon dioxide to value-added chemical fuels is an effective way to solve the energy crisis and global warming. 3 (X=Br, I) quantum dots have become a promising candidate for CO due to their excellent optoelectronic properties, including high molar extinction coefficient, low exciton binding energy, and defect tolerance. 2 However, the original MAPbX 3 (X = Br, I) QDs generally have low photocatalytic performance, which is mainly due to the dominance of charge recombination and the lack of effective CO 2 Adsorption / activation of catalytic sites.
[0003] Covalent organic frameworks (COFs) are a new type of crystalline porous organic polymers with unique properties for photocatalytic CO 2 The reduction of COFs provides an ideal platform: 1) Good chemical and thermodynamic stability ensures its robustness in the catalytic process; 2) The structure is easy to modify and functionalize, which is conducive to loading multiple types of active sites and facilitating the synthesis of functional materials based on COFs; 3) COFs are highly porous and have a large surface area, which can ensure the stability of CO 2 Adsorption and rapid mass transfer; 4) The known chemical composition and structure of COFs can provide accurate structural models, which is convenient for analyzing the reaction mechanism. However, COFs materials constructed from organic materials always lack effective active sites, which makes it difficult to achieve excellent performance as photocatalysts. Therefore, it is particularly important to develop an efficient and stable photocatalyst. Summary of the invention
[0004] In view of the shortcomings of the prior art, the first object of the present invention is to provide a method for preparing a three-dimensional covalent organic framework@metal halide perovskite composite material, so that perovskite quantum dots can be grown in situ in the pores of COF, so as to solve the problems of poor stability of perovskite quantum dots in the environment and insufficient photocatalytic activity.
[0005] The second object of the present invention is to provide a three-dimensional covalent organic framework@metal halide perovskite composite material, which has the advantage of good photocatalytic activity.
[0006] The third object of the present invention is to provide an application of a three-dimensional covalent organic framework@metal halide perovskite composite material, which can be used as a photocatalyst.
[0007] To achieve the above first object, the present invention provides the following technical solutions:
[0008] A method for preparing a three-dimensional covalent organic framework@metal halide perovskite composite material comprises the following steps:
[0009]
[0010] S1 In the first solvent, BTD and Por-8NH 2 reacting with TPDA, and then post-processing to obtain a 3DCOF material;
[0011] S2: reacting the 3D COF material obtained in S1 with lead halide in a second solvent, and after the reaction, post-processing to obtain 3D COF@PbX 2 Material;
[0012] S3: in a third solvent, the 3D COF@PbX 2 The material reacts with methylamine iodine, and after the reaction, 3D COF@MAPbX is obtained by post-treatment. 3 Composite materials.
[0013] Furthermore, in S1, the first solvent is o-dichlorobenzene, n-butanol and 8-10M acetic acid.
[0014] Furthermore, in said S1, BTD, Por-8NH are controlled 2 The mass volume ratio of TPDA, o-dichlorobenzene, n-butanol and acetic acid is 5~20mg:10~30mg:5~15mg:200~1000µL:200~1000µL:0~200µL.
[0015] Furthermore, in said S1, BTD, Por-8NH 2 and TPDA are put into a vacuum tube, and o-dichlorobenzene and n-butanol are added, ultrasonically dispersed evenly, and then acetic acid is added. After freeze-thaw degassing in 77K liquid nitrogen for 2 to 4 times, it is sealed and reacted at 100-150°C for 2 to 7 days. After the reaction is completed, the reactant is washed with DMF and / or acetone, and the washed solid is extracted with acetone for 1 to 3 days, and then vacuum dried at 50-120°C for 4 to 10 hours to obtain a 3D COF material.
[0016] Furthermore, in S2, the second solvent is N,N-dimethylformamide and ethanol, and the lead halide is a combination of one or more of lead chloride, lead bromide and lead iodide.
[0017] Furthermore, in S2, the volume ratio of N,N-dimethylformamide to ethanol is controlled to be 1:8-10, and the 3D COF material is immersed in the second solution, and the concentration of lead halide in the second solution is 0.8-1.2 mM.
[0018] Furthermore, in S2, the 3D COF material obtained in S1 is immersed in PbX 2 and the second solvent solution, and soak the reaction for 0.5-1.5 h to ensure that PbX 2 The reaction solution was centrifuged after the reaction was completed, and the solid obtained by centrifugation was washed 2 to 4 times with pure ethanol to obtain 3D COF@PbX 2 Material.
[0019] Furthermore, in S3, the third solvent is ethanol, and the solubility of methyl iodide in the third solvent is 0.8-1.2 mM.
[0020] Furthermore, in S3, the 3D COF@PbX 2 The material was immersed in a solution of methyl iodine and a third solvent for 5-15 min. After the reaction, it was washed with pure ethanol 2-4 times and vacuum dried at 40-60 °C for 4-10 h to obtain 3D COF@MAPbX 3 Composite materials.
[0021] To achieve the above second purpose, the present invention provides the following technical solutions:
[0022] A three-dimensional covalent organic framework@metal halide perovskite composite material is prepared by the preparation method.
[0023] To achieve the third objective, the present invention provides the following technical solutions:
[0024] A three-dimensional covalent organic framework@metal halide perovskite composite material is used for application. The three-dimensional covalent organic framework@metal halide perovskite composite material is prepared by the above-mentioned preparation method and is used in a photocatalyst.
[0025] In summary, the beneficial technical effects of the present invention are:
[0026] 1. The 3D COF designed and prepared in this invention has a higher specific surface area, through-holes and open active sites compared to 2D COF, and the pore size of the COF is suitable for MAPbX 3 QDs (X = Cl, Br, I) were grown in situ.
[0027] 2. The present invention provides a method for in-situ growth of MAPbX in COFs pores. 3(X = Cl, Br, I) method.
[0028] 3. The synthesis method of the present invention is simple and easy to operate and can be realized at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the NMR image of BTD of Example 1 of the present invention.
[0030] Figure 2 Por-8NH of Example 1 of the present invention 2 's NMR image.
[0031] Figure 3 This is a flow chart for preparing the 3D COF material of Example 1 of the present invention.
[0032] Figure 4 This is the XRD spectrum of the 3D COF material prepared in Example 2 of the present invention; wherein the curves shown are Bragg, Differences, Simulated, Experimental and Pawley refined from bottom to top.
[0033] Figure 5 N is the 3D COF material prepared in Example 2 of the present invention. 2 Adsorption-desorption curve diagram.
[0034] Figure 6 This is a pore size distribution diagram of the 3D COF material prepared in Example 2 of the present invention.
[0035] Figure 7 CO of the 3D COF material prepared in Example 2 of the present invention at different temperatures 2 Adsorption and desorption performance diagram.
[0036] Figure 8 3D COF@MAPbBr prepared in Example 8 of the present invention 3 XRD patterns of the composite materials.
[0037] Fig. 9 3D COF@MAPbBr prepared in Example 8 of the present invention 3 Composite material (below) and 3DCOF@MAPbI prepared in Example 9 3 TEM image of the composite material (top).
[0038] Fig.10 The 3D COF material prepared in Example 2 of the present invention and the 3D COF@MAPbBr prepared in Example 8 3 Composite material and 3D COF@MAPbI prepared in Example 9 3 UV absorption spectrum of the composite material. DETAILED DESCRIPTION
[0039] In order to make the technical means, creative features, objectives and functions achieved by the present invention clearer and easier to understand, the present invention is further explained below in conjunction with the accompanying drawings and specific implementation methods.
[0040] Example
[0041] Example 1: Reference Figures 1 to 3 , a method for preparing a three-dimensional covalent organic framework@metal halide perovskite composite material disclosed in the present invention, comprising the following steps:
[0042]
[0043] S1 In the first solvent, BTD and Por-8NH 2 reacting with TPDA, and then post-processing to obtain a 3DCOF material;
[0044] S2: In a second solvent, the 3D COF material obtained in S1 is reacted with lead halide, and after the reaction, 3D COF@PbX is obtained by post-treatment. 2 Material;
[0045] S3: The 3D COF@PbX obtained in S2 was prepared in a third solvent. 2 The material reacts with methylamine iodine, and after the reaction, 3D COF@MAPbX is obtained by post-treatment. 3 Composite materials;
[0046] In S1, the first solvent is o-dichlorobenzene, n-butanol and 8-10M acetic acid, and BTD, Por-8NH 2 , TPDA, o-dichlorobenzene, n-butanol, acetic acid mass volume ratio is 5~20mg:10~30mg:5~15mg:200~1000µL:200~1000µL:0~200µL;
[0047] In S2, the second solvent is N,N-dimethylformamide and ethanol, and the lead halide is a combination of one or more of lead chloride, lead bromide and lead iodide; the volume ratio of N,N-dimethylformamide and ethanol is controlled to be 1:8-10, and the 3D COF material is immersed in the second solution, and the concentration of the lead halide in the second solution is 0.8-1.2 mM;
[0048] In S3, the third solvent is ethanol, and the solubility of iodomethane in the third solvent is 0.8-1.2 mM.
[0049] Example 2: A method for preparing a three-dimensional covalent organic framework@metal halide perovskite composite material disclosed in the present invention, which is different from Example 1 in that the specific implementation method of S1 is:
[0050] First, 0.02mmol BTD, 0.01mmol Por-8NH 2 and 0.02mmol TPDA were put into a vacuum tube, and 400μL o-dichlorobenzene and 400μL n-butanol were added and ultrasonically dispersed evenly, and 100μL 9M acetic acid was added. After freeze-thaw degassing in 77K liquid nitrogen for 3 times, it was sealed and reacted at 120°C for 3 days. After the reaction was completed, it was immersed in a 60°C DMF solution, repeated 3 times until the supernatant was colorless, and the washed solid was stripped with acetone for 3 days, and then vacuum dried at 80°C for 12h to obtain 3DCOF material.
[0051] Example 3: A method for preparing a three-dimensional covalent organic framework@metal halide perovskite composite material disclosed in the present invention, which is different from Example 1 in that the specific implementation method of S1 is:
[0052] First, 0.02mmol BTD, 0.01mmol Por-8NH 2 and 0.02mmol TPDA were put into a vacuum tube, and 535μL o-dichlorobenzene and 265μL n-butanol were added and ultrasonically dispersed evenly, and 100μL 9M acetic acid was added. After freeze-thaw degassing in 77K liquid nitrogen for 3 times, it was sealed and reacted at 120°C for 3 days. After the reaction was completed, it was immersed in a 60°C DMF solution, repeated 3 times until the supernatant was colorless, and the washed solid was stripped with acetone for 3 days, and then vacuum dried at 80°C for 12h to obtain 3DCOF material.
[0053] Example 4: A method for preparing a three-dimensional covalent organic framework@metal halide perovskite composite material disclosed in the present invention, which is different from Example 1 in that the specific implementation method of S1 is:
[0054] First, 0.02mmol BTD, 0.01mmol Por-8NH 2 and 0.02mmol TPDA were put into a vacuum tube, and 640μL o-dichlorobenzene and 160μL n-butanol were added and ultrasonically dispersed evenly, and 100μL 9M acetic acid was added. After freeze-thaw degassing in 77K liquid nitrogen for 3 times, it was sealed and reacted at 120°C for 3 days. After the reaction was completed, it was immersed in a 60°C DMF solution, repeated 3 times until the supernatant was colorless, and the washed solid was stripped with acetone for 3 days, and then vacuum dried at 80°C for 12h to obtain 3DCOF material.
[0055] Example 5: A method for preparing a three-dimensional covalent organic framework@metal halide perovskite composite material disclosed in the present invention, which is different from Example 1 in that the specific implementation method of S1 is:
[0056] First, 0.02mmol BTD, 0.01mmol Por-8NH 2 and 0.02mmol TPDA were put into a vacuum tube, and 900μL o-dichlorobenzene and 100μL n-butanol were added and ultrasonically dispersed evenly. Then 100μL 9M acetic acid was added, and then freeze-thawed and degassed in 77K liquid nitrogen for 3 times, sealed and reacted at 120℃ for 3 days. After the reaction, it was immersed in 60℃ DMF solution, repeated 3 times until the supernatant was colorless, and the washed solid was stripped with acetone for 3 days, and then vacuum dried at 80℃ for 12h to obtain 3DCOF material.
[0057] Example 6: A method for preparing a three-dimensional covalent organic framework@metal halide perovskite composite material disclosed in the present invention, which is different from Example 1 in that the specific implementation method of S1 is:
[0058] First, 0.02mmol BTD, 0.01mmol Por-8NH 2 and 0.02mmol TPDA were put into a vacuum tube, and 480μL o-dichlorobenzene and 320μL n-butanol were added and ultrasonically dispersed evenly, and 100μL 9M acetic acid was added. After freeze-thaw degassing in 77K liquid nitrogen for 3 times, it was sealed and reacted at 120°C for 3 days. After the reaction was completed, it was immersed in a 60°C DMF solution, repeated 3 times until the supernatant was colorless, and the washed solid was stripped with acetone for 3 days, and then vacuum dried at 80°C for 12h to obtain 3DCOF material.
[0059] Example 7: A method for preparing a three-dimensional covalent organic framework@metal halide perovskite composite material disclosed in the present invention, which is different from Example 1 in that the specific implementation method of S1 is:
[0060] First, 0.02mmol BTD, 0.01mmol Por-8NH 2 and 0.02mmol TPDA were put into a vacuum tube, and 265μL o-dichlorobenzene and 535μL n-butanol were added and ultrasonically dispersed evenly, and 100μL 9M acetic acid was added. After freeze-thaw degassing in 77K liquid nitrogen for 3 times, it was sealed and reacted at 120°C for 3 days. After the reaction was completed, it was immersed in a 60°C DMF solution, repeated 3 times until the supernatant was colorless, and the washed solid was stripped with acetone for 3 days, and then vacuum dried at 80°C for 12h to obtain 3DCOF material.
[0061] Example 8: A method for preparing a three-dimensional covalent organic framework@metal halide perovskite composite material disclosed in the present invention, which is different from Example 2 in that the specific implementation of S2~S3 is:
[0062] S2: The 3D COF material obtained in S1 is immersed in 1.0 mM PbBr 2 In solution, PbBr 2 The second solvent of the solution was DMF and EtOH in a volume ratio of 1:9, and the reaction was soaked for 1.0 h to ensure that PbBr 2 After the reaction, the reaction solution was centrifuged and the solid obtained by centrifugation was washed three times with pure ethanol to obtain 3D COF@PbBr 2 Material;
[0063] S3 The 3D COF@PbBr obtained in S2 2 The material was immersed in 1.0 mM CH 3 NH 3 In I solution, CH 3 NH 3 The third solvent of solution I was ethanol, and the reaction was carried out for 10 min. After the reaction, it was washed with pure ethanol three times and dried under vacuum at 50 °C for 6 h to obtain 3D COF@MAPbBr 3 Composite materials.
[0064] Example 9: A method for preparing a three-dimensional covalent organic framework@metal halide perovskite composite material disclosed in the present invention, which is different from Example 2 in that PbX 2 PbI 2 , and obtain 3D COF@MAPbI 3 Composite materials.
[0065] Performance testing
[0066] (1) After XRD testing of the 3D COF material prepared in Example 2, the measured XRD data was imported into materialsstudio for Pawley refinement. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that the refined XRD data are basically consistent with the simulated XRD peak shape, indicating the successful synthesis of this 3D COF material.
[0067] (2) The N of the 3D COF material of Example 2 at 77K was measured successively 2 The adsorption-desorption isotherms and the corresponding calculated pore size distribution, CO at different temperatures 2 The adsorption and desorption performances are shown in Figures 5 to 7 As shown. Figure 5 and Figure 6 It can be seen that the BET specific surface area of this 3D COF material is 456.42 m 2 g -1 , the pore sizes are 3.28nm and 3.98nm. Figure 7 As can be seen from the figure, this 3D COF material has a strong affinity for CO at different temperatures. 2 All of them have certain adsorption capacity, which provides a basis for the subsequent photocatalytic CO 2 Restoration lays the foundation.
[0068] (3) The 3D COF@MAPbBr prepared in Example 8 3 Composite materials were subjected to X-ray diffraction tests, and the structure was Figure 8 As shown. Figure 8 As can be seen from the 3D COF@MAPbBr 3 Composite materials with both 3D COF and MAPbBr 3 The diffraction peaks further prove the successful preparation of this composite material.
[0069] (4) The 3D COF@MAPbBr prepared in Example 8 3 Composite material, 3D COF@MAPbI prepared in Example 9 3 The composite materials were ultrasonically dispersed in anhydrous ethanol and analyzed by transmission electron microscopy (TEM). Fig. 9 As shown, Fig. 9 (Top) 3D COF@MAPbI prepared in Example 9 3 TEM images of the composite materials. Fig. 9 (Bottom) 3D COF@MAPbBr prepared in Example 8 3 TEM image of the composite material. Figure 6 and Fig. 9 It can be seen that the average particle sizes of perovskite quantum dots measured based on GMS 3 software are 3.02 nm and 3.09 nm, respectively, which are smaller than the pore size of 3D COF, indicating that the perovskite quantum dots are successfully grown in situ within the COF pores.
[0070] (5) The 3D COF material of Example 2 and the 3D COF@MAPbBr prepared in Example 8 were 3 Composite material, 3D COF@MAPbI prepared in Example 9 3 The composite material was tested for UV diffuse reflection, and the results were as follows Fig.10 As shown. Fig.10 It can be seen that the absorption intensity of the composite material is significantly higher than that of pure COF. 3 The light-harvesting ability of the composite material is superior to that of 3D COF materials.
[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a three-dimensional covalent organic framework@metal halide perovskite composite material, characterized in that: The following steps are included: ; S1, in a first solvent, reacting BTD, Por-8NH2 and TPDA, and after the reaction, post-processing to obtain a 3D COF material; S2, reacting the 3D COF material obtained in S1 with lead halide in a second solvent, and performing post-treatment after the reaction to obtain a 3D COF@PbX2 material; S3: reacting the 3D COF@PbX2 material obtained in S2 with methylamine iodine in a third solvent, and performing post-treatment after the reaction to obtain a 3D COF@MAPbX3 composite material; In S1, the first solvent is o-dichlorobenzene, n-butanol and 8-10M acetic acid; In S1, the mass volume ratio of BTD, Por-8NH2, TPDA, o-dichlorobenzene, n-butanol, and acetic acid is controlled to be 5-20 mg: 10-30 mg: 5-15 mg: 200-1000 µL: 200-1000 µL: 0-200 µL; In the S1, BTD, Por-8NH2 and TPDA are first put into a vacuum tube, and o-dichlorobenzene and n-butanol are added, ultrasonically dispersed evenly, and then acetic acid is added. After freeze-thaw degassing in 77K liquid nitrogen for 2 to 4 times, it is sealed and reacted at 100 to 150°C for 2 to 7 days. After the reaction is completed, the reactant is washed with DMF and / or acetone, and the washed solid is stripped with acetone for 1 to 3 days, followed by vacuum drying at 50 to 120°C for 4 to 10 hours to obtain a 3D COF material.
2. The method for preparing a three-dimensional covalent organic framework@metal halide perovskite composite material according to claim 1, characterized in that: In S2, the second solvent is N,N-dimethylformamide and ethanol, and the lead halide is a combination of one or more of lead chloride, lead bromide and lead iodide; the volume ratio of N,N-dimethylformamide and ethanol is controlled to be 1:8~10, and the 3D COF material is immersed in the second solution, and the concentration of the lead halide in the second solution is 0.8~1.2mM.
3. The method for preparing a three-dimensional covalent organic framework@metal halide perovskite composite material according to claim 2, characterized in that: In S2, the 3D COF material obtained in S1 is immersed in a solution of PbX2 and a second solvent, and the reaction is carried out for 0.5 to 1.5 hours to ensure that PbX2 fully enters the pores of the 3D COF material. After the reaction is completed, the reaction solution is centrifuged, and the solid obtained by centrifugation is washed with pure ethanol for 2 to 4 times to obtain a 3D COF@PbX2 material.
4. The method for preparing a three-dimensional covalent organic framework@metal halide perovskite composite material according to claim 1, characterized in that: In S3, the third solvent is ethanol, and the solubility of methylamine iodine in the third solvent is 0.8-1.2 mM.
5. The method for preparing a three-dimensional covalent organic framework@metal halide perovskite composite material according to claim 4, characterized in that: In S3, the 3D COF@PbX2 material obtained in S2 is immersed in a solution of methylamine iodine and a third solvent, and the reaction is carried out for 5 to 15 minutes. After the reaction, it is washed with pure ethanol 2 to 4 times, and vacuum dried at 40 to 60°C for 4 to 10 hours to obtain a 3D COF@MAPbX3 composite material.
6. A three-dimensional covalent organic framework@metal halide perovskite composite material, characterized in that: The method is prepared by any one of claims 1 to 5.
7. Application of a three-dimensional covalent organic framework@metal halide perovskite composite material, characterized in that: The three-dimensional covalent organic framework@metal halide perovskite composite material is prepared by the preparation method described in any one of claims 1 to 5 and is used in a photocatalyst.
Citation Information
Patent Citations
Preparation method of metal organic framework encapsulated organic-inorganic perovskite composite photocatalytic material
CN113976174A
Cited By
Preparation method of metal halide perovskite and three-dimensional cobalt porphyrin-based COFs composite material
CN121495137A